The effect of the interphase and material properties on load transfer in fibre composites - Daadbin, A.; Gamble, A.J.; Sumner, N.D.
An interphase between a fibre and a matrix is modelled with its own mechanical properties to study the load transfer through this crucial region. The effect of material properties on the maximum shear stress during the load transfer is investigated. The results indicate an optimum point where the shear stress would be the lowest at the interphase. With the help of this model, the effect of crack initiation at the interphase on the stresses is illustrated. It is shown that cracks are likely to initiate at the fibre/interphase interface rather than at the interphase/matrix side.
Keywords: COMPOSITE MATERIALS; INTERPHASE; SHEAR STRESS; MECHANICAL PROPERTIES; CRACK INITIATION; MODELLING